Numerical study of bilge-keel effect on parametric roll and water on deck for an FPSO - Greco, Marilena; Lugni, Claudio; Colicchio, Giuseppina; Faltinsen, Odd Magnus (Volume 11: Prof. Robert F. Beck Honoring Symposium on Marine Hydrodynamics, 2015)
This research activity represents the logical continuation of the work documented in [1] and [2] on water on deck and parametric roll for an FPSO in regular waves. Here the same numerical method, based on a domain-decomposition strategy, is used to examine the platform with bilge keels, both without and with mooring-line system. It is found that bilge keels with length 40% of the ship length and with breadth the 3% of the ship breadth limit effectively the roll when instability is promoted by vertical bow motions in waves. In these conditions also the amount of the shipped water is substantially reduced. Large roll induced by the coupling with the lateral motions seems to be less well counteracted and remains close to 10° for steepness kA ≥ 0.2. This value is often set as maximum allowed amplitude for FPSOs in normal operational conditions. Also the effect on the shipped water is limited in this case. Increasing the bilge-keels breadth is confirmed to be beneficial but the combination of the mooring system with dynamic positioning appears needed for a proper control of the roll motion in the worst examined cases. acceptedVersion (c) 2015 by ASME